Dependence of the network structure of cured styrene butadiene rubber on the sulphur content - Salgueiro, Walter Alberto (2004)
An investigation about the dependence of the physical properties of styrene-butadiene rubber copolymers (cured with different sulphur content, in order to obtain various networks) on the crosslink density was carried out by means of dynamical mechanical analysis, differential scanning calorimetry and positron annihilation lifetime spectroscopy. SBR specimens were cured with different sulphur content, in order to obtain various networks. On increasing the crosslink density, the glass transition temperature increases and the fractional free volume decreases. The thermal expansion coefficient of the free volume decreases in the rubbery phase by increasing the crosslink density, owing to the slower rate of expansion of nanoholes; furthermore, it seems influenced by the percentage of polysulfide density. The density of nanoholes is independent of the temperature, but decreases on adding sulphur. The results can be framed within the Simha-Somcynsky free volume theory. © 2004 Published by Elsevier Ltd.